A stabilization fund can make the Euro area more crisis-proof - Marius Clemens; Mathias Klein (DIW Weekly Report, 2018)
Reorganizing European fiscal policy is a main topic in current reform considerations. In particular, the creation of a European stabilization mechanism is being discussed. This study examines the macroeconomic effects of a stabilization fund, the economic consequences of which are analyzed in an equilibrium model. The model shows that a stabilization fund reduces economic fluctuations and is thus a mechanism for making the entire currency area more crisis-proof in the future. However, it should be noted that a stabilization fund may be more politically feasible than shifting responsibility from the national level to a new European Ministry of Finance. Moreover, moral hazard in regards to the behavior of individual countries must be taken into account when designing the stabilization fund. For example, parallel to the introduction of a European stabilization fund, compliance with fiscal rules should be effectively enforced.
Keywords: E32; E63; F45; 330; monetary union; stabilization fund; fiscal policy